Abnormal humoral immune response to influenza vaccination in pediatric type-1 human immunodeficiency virus infected patients receiving highly active antiretroviral therapy (2007)
ABSTRACT: Given that highly active antiretroviral therapy (HAART) has been demonstrated useful to restore immune competence in type-1 human immunodeficiency virus (HIV-1)-infected subjects, we evaluated the specific antibody response to influenza vaccine in a cohort of HIV-1-infected children on HAART so as to analyze the quality of this immune response in patients under antiretroviral therapy. Sixteen HIV-1-infected children and 10 HIV-1 seronegative controls were immunized with a commercially available trivalent inactivated influenza vaccine containing the strains A/H1N1, A/H3N2, and B. Serum hemagglutinin inhibition (HI) antibody titers were determined for the three viral strains at the time of vaccination and 1 month later. Immunization induced a significantly increased humoral response against the three influenza virus strains in controls, and only against A/H3N2 in HIV-1-infected children. The comparison of post-vaccination HI titers between HIV-1+ patients and HIV-1 negative controls showed significantly higher HI titers against the three strains in controls. In addition, post vaccination protective HI titers (defined as equal to or higher than 1:40) against the strains A/H3N2 and B were observed in a lower proportion of HIV-1+ children than in controls, while a similar proportion of individuals from each group achieved protective HI titers against the A/H1N1 strain. The CD4+ T cell count, CD4/CD8 T cells ratio, and serum viral load were not affected by influenza virus vaccination when pre- vs post-vaccination values were compared. These findings suggest that despite the fact that HAART is efficient in controlling HIV-1 replication and in increasing CD4+ T cell count in HIV-1-infected children, restoration of immune competence and response to cognate antigens remain incomplete, indicating that additional therapeutic strategies are required to achieve a full reconstitution of immune functions.